Plant Growth on a Mediterranean Green Roof: A Pilot Study on Influence of Substrate Depth, Substrate Composition, and Type of Green Roof - Marouli, Christina; Savvidou, Pinelopi; Koutsokali, Maria; Papadopoulou, Paraskevi; Misseyanni, Anastasia; Tsiliki, Georgia; Georgas, Dimitris (Frontiers in Sustainable Cities, 2022)
Green roofs have been proposed as a significant method of “renaturing” the city, mitigating the urban heat island effect and controlling storm water movement. Plant growth on green roofs affects the environmental performance of the roof. Thus, it is important to examine which parameters influence this growth. Green roofs in the Mediterranean region, due to the climatic specificities of the area, have been a challenge. What types of plants are appropriate, how green roofs should be constructed and other related topics have concerned scientists in the recent years. The aim of this pilot study was to explore the growth of five plants—Sedum sediforme, Drosanthemum floribundum and Lampranthus spectabilis, Medicago arborea, and Lavandula angustifolia—on a pilot Mediterranean green roof in relation to substrate depth, organic content of substrate and type of green roof (open and modular). Data were analyzed using multiple regression with Analysis of Variance. The results indicated that substrate depth, type of green roof and substrate organic content are not significantly important parameters affecting the growth of plants and cannot predict plant performance by themselves. A main insight arising from this study is that plant communities and interspecies relations should be examined more closely in future green roof research as they may affect the impact of selected parameters on plant growth on Mediterranean green roofs. Furthermore, although the type of the green roof—open or modular—could not be directly associated with plant performance, it may be worth examining its impact on plant community performance in future studies.